Analisis Tingkat Pencemaran Air Sungai Berdasarkan Kadar Fluorida Di Kota Mataram Menggunakan Metode Spektrofotometri UV-Vis - Kholik Hidayatullah; Siti Alaa’; Hasmiyatni Hasmiyatni; Dian Wijaya Kurniawidi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
River water pollution levels can be analysed based on fluoride levels. Excessive fluoride levels will cause fluorosis of the bones. While fluoride deficiency will cause brittleness of teeth and thinning of bones. The purpose of this study was to determine the level of river water pollution based on fluoride levels in Mataram City. Fluoride levels were tested by adding a solution of zirconyl alizarin as a reagent and a solution of Na arsenite, which was then analysed by UV-Vis spectrophotometry with a wavelength of 535 nm. The results showed that the fluoride levels in the 7 tested samples met the fluoride quality standards. The highest fluoride content of river water in Mataram city is 1.046 mg/L, while the lowest is 0.213 mg/L. From this study it can be concluded that based from 7 points location water river sample in Mataram City are not polluted by fluoride.